Identification and analysis of pancreatic intraepithelial neoplasia: opportunities and challenges - Pian, Ling-ling; Song, Mei-hui; Wang, Teng-fei; Qi, Ling; Peng, Tie-li; Xie, Ke-ping (Frontiers in Endocrinology, 2025)
Pancreatic intraepithelial neoplasia (PanIN) is the most common precursor lesion of pancreatic ductal adenocarcinoma (PDAC), which has poor prognosis with a short median overall survival of 6-12 months and a low 5-year survival rate of approximately 3%. It is crucial to remove PanIN lesions to prevent the development of invasive PDAC, as PDAC spreads rapidly outside the pancreas. This review aims to provide the latest knowledge on PanIN risk, pathology, cellular origin, genetic susceptibility, and diagnosis, while identifying research gaps that require further investigation in this understudied area of precancerous lesions. PanINs are classified into PanIN 1, PanIN 2, and PanIN 3, with PanIN 3 having the highest likelihood of developing into invasive PDAC. Differentiating between PanIN 2 and PanIN 3 is clinically significant. Genetic alterations found in PDAC are also present in PanIN and increase with the grade of PanIN. Imaging methods alone are insufficient for distinguishing PanIN, necessitating the use of genetic and molecular tests for identification. In addition, metabolomics technologies and miRNAs are playing an increasingly important role in the field of cancer diagnosis, offering more possibilities for efficient identification of PanIN. Although detecting and stratifying the risk of PanIN poses challenges, the combined utilization of imaging, genetics, and metabolomics holds promise for improving patient survival in this field.